An Experimental Investigation on A Simple Direct-Drive Wavepower Generation System Utilising an Oscillating Water Column - Omar M.A.; Shokri S.; Zakaria N.M.; Mukhtar A.; Yusoff M.Z. (Institute of Physics, 2024)
This study investigates the performance potential of a simple direct-drive wavepower generation system utilising an oscillating water column (OWC). The OWC was selected due to their ability to operate in places with low wave power density, low wave height, and shallow water. This is owing to the fact that the average wave power in the Malaysian sea has been just 8.6 kW/m, which is quite low compared to other coastal nations that use wave energy technology. In this study, the OWC has been scaled down and utilised for laboratory experiments. The experiment is divided into two different parts, which are Procedure A and Procedure B. Procedure A is to determine the maximum wave height (cm), air pressure differential (psi), and upward air speed (m/s) without the air turbine installed. Procedure B, on the other hand, employs a different type of bottom profile to calculate the voltage output (V), current output (A), and power output (W). The results indicated that circular-bottomed sloped seabed is superior, as they can generate the greatest amount of electricity, approximately 0.0105 W, at air speeds of 1.3-2.0 m/s and wave heights of 4-5 cm. The findings suggested that wave energy can be harvested to operate an air turbine, but more research is needed to figure out how to convert wave energy efficiently in Malaysia, where the wave heights are smaller. 2023 Institute of Physics Publishing. All rights reserved.